2022
DOI: 10.3390/jpm12010111
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Intention to Be Vaccinated against COVID-19 in a Sample of Italian Respondents at the Start of the Immunization Campaign

Abstract: COVID-19 vaccines are the most promising means of limiting the pandemic. The present study aims at determining the roles of several psychological variables in predicting vaccination intention in Italy. An online questionnaire was disseminated between 9 March and 9 May 2021. The sample included 971 participants. Results showed that most of the participants were willing to vaccinate. Acceptance rates were correlated with age, marital status, and area of residence. Intention to be vaccinated was positively correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 49 publications
5
23
1
Order By: Relevance
“…When contrasting with other regions, the prevalence of VI found in our study was relatively higher or similar to that found in some studies conducted in European and Asian countries such as Italy (ranging from 40.1% to 78.5%) [ 42 , 43 ], France (ranging from 30.5% to 77.6%) [ 44 , 45 ], Greece (ranging from 62% to 84.8%) [ 46 , 47 ], Germany (ranging from 58% to 70%) [ 48 , 49 ], UK (ranging from 64% to 73.5%) [ 50 , 51 ], China (ranging from 28.7% to 82%) [ 52 , 53 ], or Bangladesh (ranging from 26% to 65.5%) [ 54 , 55 ]. Likewise, South Africa reported a VI lower than our estimate for LAC [ 56 ].…”
Section: Discussionsupporting
confidence: 80%
“…When contrasting with other regions, the prevalence of VI found in our study was relatively higher or similar to that found in some studies conducted in European and Asian countries such as Italy (ranging from 40.1% to 78.5%) [ 42 , 43 ], France (ranging from 30.5% to 77.6%) [ 44 , 45 ], Greece (ranging from 62% to 84.8%) [ 46 , 47 ], Germany (ranging from 58% to 70%) [ 48 , 49 ], UK (ranging from 64% to 73.5%) [ 50 , 51 ], China (ranging from 28.7% to 82%) [ 52 , 53 ], or Bangladesh (ranging from 26% to 65.5%) [ 54 , 55 ]. Likewise, South Africa reported a VI lower than our estimate for LAC [ 56 ].…”
Section: Discussionsupporting
confidence: 80%
“…Finally, it is necessary to highlight, in line with other evidence in Italy, among the socio-demographic variables, the effect on the intention to vaccine of the educational qualification and the number of vaccines already made [95]. Compared to previous research in the same context, the results of this study, on the one hand, clearly confirm that the Italian is a population, compared to others, which has shown great compliance with vaccination and a high vaccination intention [126,127].…”
Section: Discussionsupporting
confidence: 80%
“…A typical example is the Big Pharma conspiracy theory that flourished even before the COVID-19 pandemic, and what the research showed is that the fears over side effects and "unnatural" substances in vaccines are inextricably intertwined with the suspicion of the profit motive in healthcare (Paul et al, 2020). In the context of COVID-19, both conspiracy mentality and the anti-scientific sentiments are shown to negatively predict guideline adherence and vaccine intentions (Bertin et al, 2020;Marinthe et al, 2020;Hromatko et al, 2021;Santirocchi et al, 2022). Evidently, anti-scientific rhetoric bears serious consequences for both, individual health and health of the community.…”
Section: Discussionmentioning
confidence: 99%